The potential impact of the Optional Protocol to the International Covenant on Economic, Social and Cultural Rights on the realisation of socio-economic rights in the international arena: what can be learnt from the justiciability of socio-economic rights in South Africa? - Galliker, Doris (Department of Public Law, 2014)
The Optional Protocol to the International Covenant on Economic, Social and Cultural Rights (the 'Optional Protocol' or the 'OP-ICESCR') has recently been adopted by the General Assembly of the United Nations. This document establishes a new complaints procedure for economic, social and cultural rights ('ESCR') within the United Nations human rights system. Hence, those rights ' as it is already the case for civil and political rights (CPR) ' will become quasi-justiciable at international level. Once the Optional Protocol will enter into force, individuals and groups victims of violations of any right contained in the International Covenant on Economic, Social and Cultural Rights (the 'Covenant' or the 'ICESCR') will have the possibility to submit communications to the United Nations Committee on Economic, Social and Cultural Rights (the 'Committee' or the 'CESCR'), as long as the state concerned is party to the OP-ICESCR.